2016
DOI: 10.1016/j.fertnstert.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes decline with increasing body mass index: analysis of 239,127 fresh autologous in vitro fertilization cycles from the 2008–2010 Society for Assisted Reproductive Technology registry

Abstract: Success rates in fresh autologous cycles, including those done for specifically PCOS or male-factor infertility, are highest in those with low and normal BMIs. Furthermore, there is a progressive and statistically significant worsening of outcomes in groups with higher BMIs. More research is needed to determine the causes and extent of the influence of BMI on IVF success rates in other patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
137
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 31 publications
12
137
1
5
Order By: Relevance
“…They also had significantly less oocytes retrieved, if compared with women with normal BMI, and correcting by age, although this is of little clinical significance. Cancellation rates were four-fold higher in obese patients than in women with a BMI < 30kg/m 2 ; however, this was much lower than cancellation rates reported by Provost et al (2016) . Pinborg et al (2011) also showed an increase in the likelihood of cycle cancellation, after adjusting for age.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…They also had significantly less oocytes retrieved, if compared with women with normal BMI, and correcting by age, although this is of little clinical significance. Cancellation rates were four-fold higher in obese patients than in women with a BMI < 30kg/m 2 ; however, this was much lower than cancellation rates reported by Provost et al (2016) . Pinborg et al (2011) also showed an increase in the likelihood of cycle cancellation, after adjusting for age.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, in the other large multicentric studies, undertaken in the USA, only 16.5% and 17.8% of patients undergoing ART were obese ( Luke et al. , 2011 ; Provost et al , 2016 ). This issue could be explained because of the rapid epidemiological changes in most developing countries over the last decades, with a nutritional transition, which impacts on the quality of food, resulting in a declining of malnutrition rates, but an increase in overweight and obesity ( Rivera et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, obese women under treatment for infertility may face additional problems, such as the need for higher doses of drugs to induce/stimulate ovulation, oocyte morphological changes, reduction in fertilization and implantation rates, and embryo quality (ASRM, 2015; Provost et al ., 2016). Compared to women of normal body weight, obese women submitted to IVF may present reduced rates of clinical pregnancy and live births, with an increased rate of abortion (Provost et al ., 2016). In addition, obese pregnant women have a higher incidence of maternal and fetal complications, such as gestational diabetes, hypertensive disorders of pregnancy and increased perinatal morbidity/mortality (Aune et al ., 2014).…”
mentioning
confidence: 99%